Potential phytotoxic and shading effects of invasive Fallopia (Polygonaceae) taxa on the germination of native dominant species - Lenka Moravcová; Petr Pyšek; Vojtěch Jarošik; Petr Zákravský (NeoBiota, 2011)
Two species of knotweeds (genus Fallopia, Polygonaceae), native to Asia (Fallopia sachalinensis, F. japonica) and their hybrid (F. ×bohemica) belong to the most noxious plant invaders in Europe and exert a high impact on invaded plant communities that are therefore typically extremely poor in species. The remarkable paucity of invaded communities points to the possible existence of mechanisms suppressing germinating populations of native species in invaded stands. In this pilot study we assessed, under laboratory conditions, whether there are phytotoxic effects of the three Fallopia congeners on seed germination of three target species: two native species commonly growing in habitats that are often invaded by knotweeds (Urtica dioica, Calamagrostis epigejos), and Lepidium sativum, a species commonly used in allelopathic bioassay as a control. Since knotweeds generally form stands with a high cover, we included varying light conditions as an additional factor, to simulate the effects on germination of shading by leaf canopy. The effects of aqueous extracts (2.5, 5.0%, and 0% as a control) from dry leaves and rhizomes of the Fallopia congeners on germination of the target species were thus studied under two light regimes, simulating full daylight (white light) and light filtered through canopy (green light), and in dark as a control regime. Rhizome extracts did not affect germination. Light treatments yielded inconclusive results, indicating that poor germination and establishment of species in invaded stands is unlikely to be caused by shading alone, but we found a pronounced phytotoxic effect of leaf extracts of Fallopia taxa, more so at 5.0% than 2.5% extract concentration. Fallopia sachalinensis exerted the largest negative effect on the germination of Urtica dioica, F. ×bohemica on that of C.epigejos, and F. japonica had invariably the lowest inhibitory effect. In the field in Central Europe, F. sachalinensis often invades less disturbed, moist riparian-like habitats where it often encounters U. dioica populations, while F. ×bohemica tends to occur more often in ruderal sites with a high representation of C. epigejos; this might imply that each of the knotweed species exhibits a stronger effect on native species that are dominant in habitats they typically invade. The weakest phytotoxic effect of F. japonica corresponds to the results of previous studies that found this species to be generally a weaker competitor than its two congeners. Although the results of our experiments cannot be taken as a direct evidence for allelopathic effects acting in the field, the demonstrated potential phytotoxic effect of invasive Fallopia species on the germination of native species suggests that allelopathy may play a role in the strong impact of knotweed invasion on species diversity of invaded communities observed in the field.